2010
DOI: 10.1002/rcm.4698
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of alkylamine ethoxylates (ANEOs) in commercial herbicide formulations using liquid chromatography/electrospray ionisation mass spectrometry

Abstract: A quantitative method is described for the characterization of alkylamine ethoxylate (ANEO) surfactants in commercial herbicide formulations using reversed-phase high-performance liquid chromatography with electrospray ionization mass spectrometric detection. The proposed protocol allows the simultaneous determination of a full range of oligomers which were monitored as [M-H](+) ions in positive ion mode. The instrumental detection limits (LODs) were 0.5 µg. The method developed was successfully applied to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The mass differences of neighboring oligomers are 44.03 and 58.04 amu, respectively, for an EO and PO unit. A TSS oligomer with a longer EO chain has a reduced retention time on a reversed phase column (Figure B–E), which is similar to other nonionic surfactants . A PO unit further enhances hydrophobicity, and oligomers with increasing PO units have increased retention time (Figure A).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The mass differences of neighboring oligomers are 44.03 and 58.04 amu, respectively, for an EO and PO unit. A TSS oligomer with a longer EO chain has a reduced retention time on a reversed phase column (Figure B–E), which is similar to other nonionic surfactants . A PO unit further enhances hydrophobicity, and oligomers with increasing PO units have increased retention time (Figure A).…”
Section: Resultsmentioning
confidence: 60%
“…A TSS oligomer with a longer EO chain has a reduced retention time on a reversed phase column (Figure 2B−E), which is similar to other nonionic surfactants. 27 A PO unit further enhances hydrophobicity, and oligomers with increasing PO units have increased retention time (Figure 2A). Combining mass spectral and retention behavior, a prediction for the ratio of EO/PO units in the side chain can be obtained.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…These results demonstrated that the present QuEChERS-HILIC-MS method was suitable for the determination of POE-tallowamine homologs from various citrus matrices. It has been reported that a maximum of 15 homologs of C16s, C18s, and C18u were detected in previous analytical studies ( 12 , 14 ). However, the proposed method allowed us to simultaneously and selectively determine 66 POE-tallowamine homologs, significantly improving the high-throughput analysis of POE-tallowamine.…”
Section: Resultsmentioning
confidence: 87%
“…The environmental fate and effects of glyphosate have been widely studied, but there has been much less research published on POEA. , There are also very few analytical methods for POEA in the literature, , and only one that analyzes for a wide spectrum of EO distributions for the most abundant tallow moieties . The environmental effects of some other surfactants have been studied including alkylphenol ethoxylates because of the potential toxicity and endocrine disrupting properties of the alkylphenol ethoxylates degradation products such as nonylphenol, linear alkylbenzenesulfonates because of their widespread use, and organosilicone surfactants because they might be contributing to declining bee populations …”
Section: Introductionmentioning
confidence: 99%